Enantioselective intramolecular decarboxylative C-H bond func-tionalization of quinazolinones with amino acids by visible light photoredox catalysis - Sonavane, Sameer R.; Mhaske, Santosh B. (Chemistry-An Asian Journal, 2023)
The direct visible light-mediated intramolecular decarboxylative C-H functionalization of Csp(2)-H bond adjacent to the nitrogen of a heteroarene has been achieved by iridium-catalyzed photodecarboxylative radical cyclization. This method offers rapid entry to the synthesis of quinazolinone scaffolds from easily accessible starting materials. The newly developed protocol is mild, operationally simple, oxidant free and general. The utility of this unique Csp(3)-Csp(2) bond forming reaction has been demonstrated in the syntheses of Circumdatin, Sclerotigenine and Benzomalvin A class of quinazolinone natural products and their congeners. The present work represents an interesting example of use of memory of chirality in decarboxylative C-C bond forming enantioselective photoredox reaction.
Keywords: C-H functionalization; memory of chirality; Minisci reaction; photodecarboxylative cyclization; photoredox catalysis; quinazolinone alkaloid; Radical